INTERMEDIATE LAND RIGHTS TRANSFER SYSTEM INDONESIA AND BRUNEI DARUSALAM - Jhon Tyson Pelawi; Ismansyah Ismansyah; Muhammad Yamin; Marlina Marlina (Green Publisher, 2023)
The certificate of land itself is a strong proof of ownership. This is regulated in Article 19 paragraph (2) letter c of the UUPA which states that land registration ends with the granting of letters of proof of rights, which apply as a strong evidentiary tool. There are differences in the legal system of the transfer of land rights between Indonesia and Brunei Darussalam in terms of utilizing the function and management of land as a basis for the welfare of the people. This study aims to analyze and form the concept of criminal law on land. Through normative legal research or literature law research using a juridical approach using the theory of legal objectives in analyzing problems. The results of the study that the Indonesian legal system has undergone a number of major changes to build an integrated national legal system, which is based on Pancasila and the 1945 Constitution and the legal system in Brunei Darussalam based on the British huku system with a combination of the Shari'a system for Muslims. That the transfer of land rights in the legal system in Indonesia which is regulated in Article 26 of UUPA Number 5 of 1960 and Brunei Darussalam grants property rights status to foreign nationals based on Brunei Darussalam Land Code Cap. 40 and Land Cap. 41 of 1984